Union Density Effects on Productivity and Wages. Issue 631 (24th April 2020) - Barth, Erling; Bryson, Alex; Dale-Olsen, Harald
Abstract: We exploit changes in tax subsidies for union members in Norway to identify the effects of changes in firm-level union density on productivity and wages. Increased deductions in taxable income for union members led to higher membership rates and contributed to a lower decline in union membership rates over time in Norway. Accounting for selection effects and the potential endogeneity of unionisation, the results show that increasing union density at the firm level leads to a substantial increase in both productivity and wages. The wage effect is larger in more productive firms, consistent with rent-sharing models.